Preliminary decision-making procedures in financial law matters in countries that joined in 2004 - Tóth-Lakos, Fruzsina Anna (Public Finance Quarterly, 2025)
The aim of this study is to show the proportion of cases in which the courts of the countries that joined the European Union in 2004 (Cyprus, the Czech Republic, Estonia, Poland, Latvia, Lithuania, Hungary, Malta, Slovakia, and Slovenia) have referred ﬁnancial law issues to the Court of Justice of the European Union for preliminary rulings, and the types of cases in which they have sought guidance. In the introduction, I discuss whether there is such a thing as a European tax, and then I go on to discuss the importance of the case law developed by the Court of Justice of the European Union in the ﬁeld of ﬁnancial law. The research method is based on a statistical analysis of search results using keywords speciﬁed on the website https://curia.europa.eu. I ﬁltered the available data and information based on requests for advance rulings on customs cooperation, customs valuation, common customs tariﬀ, customs union, indirect taxation, excise duties, value added tax, internal taxation, and taxation. As a result, I used a ratio to compare the data and grouped the motions into diﬀerent categories. If a case is interesting or noteworthy from any point of view, or if it has an impact on the practice of tax authorities or courts, I highlight the facts of the case or its theoretical signiﬁcance. I then summarized my general and substantive legal conclusions, from which I drew my ﬁnal conclusion.